Chromatin Imbalance as the Vertex Between Fetal Valproate Syndrome and Chromatinopathies - Parodi, Chiara; Di Fede, Elisabetta; Peron, Angela; Viganò, Ilaria; Grazioli, Paolo; Castiglioni, Silvia; Finnell, Richard H.; Gervasini, Cristina; Vignoli, Aglaia; Massa, Valentina (Frontiers in Cell and Developmental Biology, 2021)
Prenatal exposure to valproate (VPA), an antiepileptic drug, has been associated with Fetal Valproate Spectrum Disorders (FVSD), a clinical condition including congenital malformations, developmental delay, intellectual disability as well as autism spectrum disorder, together with a distinctive facial appearance. Valproate is a known inhibitor of histone deacetylase (HDAC) which regulates the chromatin state. Interestingly, perturbations of this epigenetic balance are associated with chromatinopathies, a heterogeneous group of Mendelian disorders arising from mutations in components of the epigenetic machinery. Patients affected from these disorders display a plethora of clinical signs, mainly neurological deficits and intellectual disability, together with distinctive craniofacial dysmorphisms. Remarkably, critically examining the phenotype of FVSD and chromatinopathies, they shared several overlapping features that can be observed despite the different etiologies of these disorders, suggesting the possible existence of a common perturbed mechanism(s) during embryonic development.